Dampak Covid-19 terhadap Perekonomian Masyarakat Ditinjau dari Perspektif Ekonomi Syariah - Batubara, Yennika; Yafiz, Muhammad; Batubara, Maryam (Faculty of Islamic Economics and Business Sultan Aji Muhammad Idris State Islamic University Samarinda, 2022)
The Covid-19 pandemic has brought significant changes in social, political, and economic orders at various levels, causing a global recession marked by rising unemployment​​. The purpose of this study was to find out how big the impact of the covid-19 virus was on the economy of the people in the city of Medan, how did the people of the city of Medan anticipate being able to carry out their lives and how did the Medan city government take action to deal with the covid-19 virus. Data collection and retrieval was carried out by means of field research through observation and interviews with direct companies and obtained from respondents through questionnaires, focus groups, panels and data from the results of direct interviews with researchers with informants and direct observation of the object or company where the author conducted the research and analysed using triangulation technique. The findings show that economic growth which resulted in an almost recession and greatly decreased made all economic activists feel threatened by the spread of the pandemic, because it resulted in limited activities and unusual economic activity. Islamic economics guarantees private ownership but also prioritizes common interests. So that private property can be used to help many people and be of benefit to others. The downturn in the Indonesian people's economy has also resulted in several outlets, or companies causing bankruptcy, and even dismissals have occurred in various companies which have also resulted in unemployment everywhere. The article implies that the COVID-19 pandemic has significantly worsened the economic conditions in Medan, resulting in decreased income and increased unemployment, particularly in the MSME sector. This highlights the importance of implementing Sharia economic policies as a solution to enhance the welfare and economic resilience of the community by providing stronger support to the most affected sectors.